1992
DOI: 10.1073/pnas.89.23.11431
|View full text |Cite
|
Sign up to set email alerts
|

Reading-frame restoration with an apolipoprotein B gene frameshift mutation.

Abstract: We emined a mutant human apolipoprotein B (apoB) allele that causes hypobetalipoproteinemia and has a single cytosine deletion in exon 26. This fameshift mutation was associated with the synthesis of a truncated apoB protein of the predicted size; however, studies in human subjects and minigene expression studies in cultured cells indicated that the mutant allele also yielded a full-length apoB protein. The 1-base-pair deletion in the mutant apoB allele created a stretch of eight consecutive adenines. To under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 33 publications
0
43
0
Order By: Relevance
“…This finding is not observed in heterozygous or wild-type mice. Steinberg and co-workers (9) have reported fasting chylomicronemia in a human with HBL; and plasma from Steinberg's human subject, a compound heterozygote with one mutant allele yielding apoB37 and another mutant allele yielding apoB86 (29), is compared with the mouse plasma in Fig. 5 to illustrate this.…”
Section: Resultsmentioning
confidence: 99%
“…This finding is not observed in heterozygous or wild-type mice. Steinberg and co-workers (9) have reported fasting chylomicronemia in a human with HBL; and plasma from Steinberg's human subject, a compound heterozygote with one mutant allele yielding apoB37 and another mutant allele yielding apoB86 (29), is compared with the mouse plasma in Fig. 5 to illustrate this.…”
Section: Resultsmentioning
confidence: 99%
“…thermophilus RNA polymerase appears to function similarly to E. coli RNA polymerase in adding or deleting A͞T residues by simple realignment of the template with the nascent transcript. This also appears to be the mechanism for transcriptional slippage in an apolipoprotein B mutant that contains a run of eight As (31,32) and in the expression of multiple lipooligosaccharides in Neisseria gonorrhoeae due to a polyguanine tract (33). In cases of transcriptional slippage in paramyxoviruses, the number of added residues is controlled by a signal positioned immediately 5Ј to the insertion site (34,35).…”
Section: Resultsmentioning
confidence: 99%
“…Additional observations of transcriptional slippage on homopolymeric tracts have been reported in bacteriophages (10), prokaryotes (11)(12)(13)(14), viruses (15), and eukaryotes (16,17). A clear demonstration of in vivo transcriptional slippage during elongation was provided by Wagner et al (18), who showed that Escherichia coli RNA polymerase made slippage RNA products from templates with a homopolymeric tract greater than 9 nucleotides.…”
mentioning
confidence: 86%